2012
DOI: 10.3390/toxins4111139
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Induction by OTA and TNF-α in Cultured Primary Rat Hepatocytes and Prevention by Silibinin

Abstract: In cultures of primary rat hepatocytes, apoptosis occurred after application of 20 ng/mL tumor necrosis factor alpha (TNF-α). However, this was only in the presence of 200 ng/mL of the transcriptional inhibitor actinomycin D (ActD). This toxic effect was completely prevented in the presence of 25 µg/mL soluble TNF-α receptor I (sTNFR I) in the supernatant of hepatocyte cell cultures. Apoptosis also occurred after application of 12.5 µmol/L ochratoxin A (OTA). However, that was not prevented by up to 500 µg/mL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 48 publications
1
17
0
1
Order By: Relevance
“…At these concentrations, silibinin at the concentration range from 0.9 to 109 µM was added to evaluate its preventive effect in extended range of recommended daily dose of the supplement. As previously published, the co-treatment with both silibinin and mycotoxins did not improve the cell growth, but pretreatment of the cells by silibinin for 2 h before mycotoxins addition protected the cells against mycotoxins-mediated apoptosis [41,42]. Thus, we chose this approach to evaluate the protective effect of silibinin against mycotoxins-induced cytotoxicity.…”
Section: Suppression Of Mycotoxins' Acute Toxicity By Silibininmentioning
confidence: 94%
See 3 more Smart Citations
“…At these concentrations, silibinin at the concentration range from 0.9 to 109 µM was added to evaluate its preventive effect in extended range of recommended daily dose of the supplement. As previously published, the co-treatment with both silibinin and mycotoxins did not improve the cell growth, but pretreatment of the cells by silibinin for 2 h before mycotoxins addition protected the cells against mycotoxins-mediated apoptosis [41,42]. Thus, we chose this approach to evaluate the protective effect of silibinin against mycotoxins-induced cytotoxicity.…”
Section: Suppression Of Mycotoxins' Acute Toxicity By Silibininmentioning
confidence: 94%
“…According to Naseer et al [38], silymarin showed better results compared to choline chloride (liver tonics) in lowering the AFB1-induced serum aminotransferase, creatinine, and blood urea nitrogen. Silibinin has received much attention, but the negation of mycotoxins toxicity by silibinin has only been achieved on primary rat hepatocytes, isolated rat Kupffer cells, calves, and mice [37,38,[40][41][42].…”
Section: Mycotoxins Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary hepatocytes may be suitable for a liver model to speculate about antioxidant mechanisms in the liver (17), in which parts of liver functions reportedly decrease gradually (18), and, in view of animal welfare, sacrifice of animals to obtain primary hepatocytes should be replaced by other models if the models do not have crucial defects. As a model of mammalian hepatocytes, therefore, HepG2 human hepatoma cells were used in this study because HepG2 cells stably express MAPK and related proteins and show responses to oxidative stress similarly to those of in vivo studies despite the lack of some liver functions (6,10,19).…”
Section: Methodsmentioning
confidence: 99%